Hydrogenation of furfural by noble metal-free nickel modified tungsten carbide catalysts. Issue 46 (22nd July 2020) - Bretzler, Patrick; Huber, Michael; Nickl, Simon; Köhler, Klaus
Abstract : Furfural is converted over a noble metal-free, nickel modified tungsten carbide catalyst to high value products, including 1, 2-pentanediol. Abstract : Nickel–tungsten carbide catalysts convert furfural to high value products in a liquid phase catalytic reaction. The product distribution depends on the solvent and the Ni–W-ratio of the catalyst. In isopropyl alcohol a combination of Ni and W x C enables the opening of the furan ring to yield 1, 2-pentanediol. Nickel accelerates the tungsten oxide reduction in the tungsten carbide catalyst synthesis and facilitates the carbon insertion. Nickel modified tungsten carbide is a promising, noble metal-free catalyst system for the upgrading of furfural based renewable resources. Its preparation is facilitated compared to unmodified tungsten carbide catalysts.